Meningkatkan Literasi Masyarakat Melalui Pemberdayaan dan Pembentukan Perpustakaan Desa di Balai Desa Batu Putih Sumenep - Wahdian, Agus; Hardiansyah, Framz (Welfare : Jurnal Pengabdian Masyarakat, 2023)
The government system in Indonesia, village/ward, is the lowest organizational unit of Government. The rural population is the essential capital of development. Batu Putih Kenek is a village area with a population that is classified as not too dense; through the latest data obtained from the village office and the results of interviews with the head and village officials obtained data on the population of Batu Putih Kenek Village, namely 2,965 people with details through gender, namely by population male = 1,390 people and female population = 1,573. The method used is the Palricipal Rural Alpralization (PRAl) which is simply the PRAl method is defined as a method in the process of capitalizing on malsyalralkalt by maintaining the awareness of active palsipalsial malsyalralkalt. Even though the library has a significant and strategic role as a partner in supporting the national goal, namely educating the nation's life, the allocation of funds for library development still needs to be improved.